2004
DOI: 10.1080/00016470410001295
|View full text |Cite
|
Sign up to set email alerts
|

High local concentrations without systemic adverse effects after impaction of netilmicin-impregnated bone

Abstract: Background When cancellous bone is impregnated with antibiotics the subsequent release of antibiotics from the bone shows a high early release. Hence, impaction of large amounts of netilmicin-impregnated bone may cause toxic netilmicin values in serum.Patients and methods We studied kidney and otovestibular function after impacting 50 g of netilmicin-impregnated cancellous bone during revision hip or knee arthroplasty in 20 patients. The bone was impacted in the acetabulum (n = 8), proximal femur (n = 9) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
(27 reference statements)
0
27
0
3
Order By: Relevance
“…In vitro studies have shown that a high level of tobramycin (400 mg/L) impairs cell replication (Miclau et al 1995). However, no systemic adverse effects were observed in patients operated with impaction of netilimicinimpregnated cancellous bone (Witsø et al 2004). In an experimental study in rats, Gray and Elves (1981) observed that topically applied antibiotic powder was detrimental to the osteogenesis in fresh corticocancellous isograft.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that a high level of tobramycin (400 mg/L) impairs cell replication (Miclau et al 1995). However, no systemic adverse effects were observed in patients operated with impaction of netilimicinimpregnated cancellous bone (Witsø et al 2004). In an experimental study in rats, Gray and Elves (1981) observed that topically applied antibiotic powder was detrimental to the osteogenesis in fresh corticocancellous isograft.…”
Section: Discussionmentioning
confidence: 99%
“…Witso et al used netilmicin-impregnated allografts for reconstruction in revision hip and knee surgery and found no adverse effects (22). Buttaro et al (23) favorably used vancomycin supplemented cancellous grafts for reconstruction after infected THA (20,23 (24,25).…”
Section: Justificationmentioning
confidence: 99%
“…One hour is an acceptable period for antibiotic impregnation allowing the procedure to be done during surgery. Studies in the related literature have shown that one hour antibiotic impregnation provides effective antibiotic impregnation to bone [3,4]. Our model was the establishment of early deep implant related infection; thus, it is not prerequisite to remove a stable implant which would inevitably increase the morbidity in clinical applications.…”
mentioning
confidence: 99%